Epidemicity and clonal replacement of hypervirulent carbapenem-resistant Klebsiella pneumoniae with diverse pathotypes and resistance profiles in a hospital. (March 2023) - Tang, Na; Li, Yi; Yao, Shigang; Hu, Jinshu; Zhao, Yingying; Fu, Songzhe; Song, Yuqin; Wang, Chao; Zhang, Gang; Wei, Dawei; Li, Chao; Jia, Rufu; et al.
Highlights: Three CR-hvKP ST11 clones that emerged in a hospital contain diverse virulence and resistance genes. Three clones gradually replaced each other in this hospital. The strains of clade B show enhanced virulence potential and dominate the hospital. Abstract: Objectives: The emergence of carbapenem-resistant and hypervirulent Klebsiella pneumoniae (CR-hvKP) poses a great threat to public health. There is a paramount need to increase awareness of the epidemiology, evolution, and pathogenesis of CR-hvKP. Methods: We collected strains of K. pneumoniae for over two years in a hospital. CR-hvKP strains were screened by polymerase chain reaction (PCR) with primers targeting the virulence genes. Genome sequencing was used to determine phylogenetic relationships and genetic characterization of virulence elements. The population dynamics within these strains were analyzed through epidemiological data. The string test, siderophore secretion, and murine infection experiments were performed to investigate virulence potential of different clones. Results: A total of 1172 K. pneumoniae strains were isolated from 817 patients, and 125 isolates were identified as CR-hvKP. In all, 102 CR-hvKP strains belonged to sequence type (ST) 11. Genomic analysis demonstrated that three clones of ST11 successively replaced each other in the hospital. Among them, the strains of clade A and clade B acquired virulence plasmids and the strains of clade C acquired a new integrating conjugative element (ICE). Phenotypic experiments revealed enhanced virulence potential of the recent epidemic clone from clade B. Sequence type 11 strains were favorable hosts for the convergence of virulence and resistance, indicated by clonal replacement and acquisition patterns of virulence elements. Conclusion: The emergence of the enhanced virulence potential of ST11 CR-hvKP suggests that coevolution between hosts and exogenous factors can produce super-virulent CR-hvKP strains, highlighting the need to closely monitor changes in the virulence characteristics of CR-hvKP.